What is the LIGHT THAT TOUCHES US? Stage lighting and black skin (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This article is the result of a Final Course Project (TCC) and aims to present and reflect on my first practices as a stage lighting technician focusing on black bodies, based on the current visual structures and how they influence the construction of narratives and stereotypes that favor or not certain bodies when faced with the reproduction of images. Constructing forms of representation that directly influence the creation of stage lighting in shows, performances and other types of artistic manifestations about the black body. Having as its main field of research the Coletivo NEGA (Negras Experimentações Grupo de Artes). This study strives to contribute to a conversation between the fields of Theater, Lighting and Postcolonial Studies.
Keywords: black theater; NEGA collective; stage lighting; black skin